Starch film incorporated with cinnamon oils optimally prepared by using response surface methodology - Ummi Habibah Abdullah; Muhammad Jefri Mohd Yusof; Ainon Hamzah; Ishak Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
Recent progress in the food industry emphasizes on active packaging that integrates antimicrobial feature into food packaging made from biodegradable films. In this study, antimicrobial films were prepared from starch biopolymer incorporated with cinnamon oil as antimicrobial agent. Many studies have reported on the increasing antimicrobial properties of biofilms when the concentration of antimicrobial agent is increased, yet their tensile strength would be lowered. Therefore, the preparation of these films requires comprehensive optimization to ensure optimum properties of the resulting films. The aim of this study was to optimize the mechanical and antimicrobial property of film after adding cinnamon oil using response surface methodology (RSM). The optimization of variables to prepare the films was successfully accomplished by manipulating cinnamon oil loadings and mixing temperature as proposed by RSM. Several models were generated to associate those parameters with the responding variables such as tensile strength and antimicrobial activity against Bacillus cereus, Bacillus subtilis, Aspergillus niger, and Aspergillus brasiliensis with R2 values of 0.9835, 0.9816, 0.9709, 0.9930, and 0.9950, respectively. Subsequently, the optimum conditions for the preparation of starch/cinnamon oil films were found to be at 24.02% of cinnamon oil and 49.35 °C of mixing temperature. Our study has demonstrated a novel, statistical experimental design and elaborate discussion on the effects of processing parameters in preparing films composing of starch and cinnamon oil. In summary, the active films prepared from this study have displayed promising qualities as potential food packaging against most common food borne microorganism during the food storage.